Pengaruh Kualitas Produk dan Inovasi Terhadap Daya Saing UMKM Keripik Balado di Kota Padang - Novia, Aviva Atma; Luwiensky, Lorenz Kintana; Saris, Anggye Octha Mhanyang (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in driving regional economic growth and strengthening the national economic structure. In the city of Padang, balado crisps are one of the signature culinary products developed through the MSME sector; however, the increasing number of businesses has led to fiercer competition, thereby necessitating an improvement in competitiveness. This study aims to analyse the influence of product quality and innovation on the competitiveness of balado chips MSMEs in the city of Padang. The study employs a quantitative approach with an explanatory research design. Primary data was obtained through the distribution of questionnaires to balado chips MSME operators using a Likert scale. Data analysis was conducted using multiple linear regression to test the influence of product quality and innovation on business competitiveness. The results indicate that product quality and innovation have a positive and significant impact on the competitiveness of balado chip SMEs. Improvements in raw material quality, flavour consistency, and innovations in product variants and packaging have proven effective in strengthening the competitive position of SMEs in the market. These findings indicate that the development of product quality and innovation are key factors in enhancing business competitiveness. Therefore, SME operators need to continuously improve quality and pursue innovation in a sustainable manner to remain competitive and thrive in an increasingly dynamic market.